2004
DOI: 10.1002/cpa.20022
|View full text |Cite
|
Sign up to set email alerts
|

Mean curvature flows and isotopy of maps between spheres

Abstract: Let f be a smooth map between unit spheres of possibly different dimensions. We prove the global existence and convergence of the mean curvature flow of the graph of f under various conditions. A corollary is that any area-decreasing map between unit spheres (of possibly different dimensions) is isotopic to a constant map.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 23 publications
(52 reference statements)
4
39
0
Order By: Relevance
“…for some positive number 0 > σ , is homotopic to a constant map. Other vanishing theorems can be found in [21] and [30]. In the fourth section of our paper we prove that any harmonic contraction mapping between a compact Riemannian manifold ( with respect to the local coordinates of U and U .…”
mentioning
confidence: 79%
“…for some positive number 0 > σ , is homotopic to a constant map. Other vanishing theorems can be found in [21] and [30]. In the fourth section of our paper we prove that any harmonic contraction mapping between a compact Riemannian manifold ( with respect to the local coordinates of U and U .…”
mentioning
confidence: 79%
“…Now we have already shown that |λ i | ≤ 1−δ for some δ. By the theorem in [Tsui and Wang 2004] we know that this condition can be preserved along the mean curvature flow. After putting this into Equation (2-1), its right side term in parentheses becomes…”
Section: Long Time Existencementioning
confidence: 92%
“…Claim When t ≥ T 0 , ||B|| 2 ≤ c 19 e −τ t for some positive constants c 19 and τ . We prove the claim.…”
Section: Proofmentioning
confidence: 99%